Efficiency and ergonomic benefits of using radio controlled chokers in cable yarding - Leitner, T.; Visser, R.; Stampfer, K. (University of Canterbury. School of Forestry, 2009)
Using radio controlled chokers in cable yarding can improve both productivity and safety during the unhooking phase part of the extraction cycle. However, the additional weight of the radio controlled chokers may also increase the work load of the choker-setters on the slope. A study has been completed in Austria on the Wanderfalke yarder. The factorial study design alternated extraction corridors with and without the use of radio controlled chokers. A standard choker for this system weighs 0.34 kg and cost 11 Euro each, whereas the radio controlled chokers weighs 1.6 kg and cost 9,000 Euros for the set of four chokers. Work-load was measured by continuously monitoring the heart-rate of the workers. Results showed that was a slight productivity gain, but also an increased work-load for the choker-setter. This is reflected in the comments from the yarder crew; the yarder operator thinks it great not having to get down to unhook the turn, the choker-setter is not impressed with the extra weight and work load.